Photographs of views of Sydney, 1842 - Rae, John, 1813-1900. (Sydney : Charles Potter, Government Printer, 1893)
Album includes photographic reproductions of watercolours painted by the artist in 1842 and 1850. Images include streets, parks, churches, dwellings and views around the harbour in the Sydney.
Rex Nan Kivell Collection NK7169
Also available online
John Rae, 1813-1900, public servant, author and painter, migrated to Australia in 1839 to work in Sydney. Rae was also a talented amateur artist. He painted water-colours of Sydney streets, taught himself photography and used it to record details for later paintings and his camera obscura contributed to his panorama of Sydney Harbour. He also produced large panoramas of Wollongong, Newcastle and part of the Murray Valley. His sketches of colonial scenes were sent to the Calcutta Exhibition in 1883 and to the Centennial International Exhibition, Melbourne, in 1888. In 1900 the Bulletin praised his collection of views of old Sydney.
Keywords: Sydney (N.S.W.) -- Photographs; Sydney (N.S.W.) -- History -- 1788-1851.